Proactive and Participatory Governance Model for Effective Traffic Asset Management of the Ponorogo Transportation Agency - M. Rama Kukuh Prayoga; Fedianty Augustinah; Priyanto Priyanto (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study examines the effectiveness of public service management in Ponorogo Regency's transport sector, focusing on the performance gap between traffic asset conditions (signs, traffic lights) and formal maintenance policies. This gap indicates a non-proactive maintenance cycle, exacerbated by limited resources and low organisational responsiveness to public complaints. Employing a qualitative case study grounded in a synthesis of Edwards III's Policy Implementation Theory and the New Public Service (NPS) perspective, the core findings confirm that frontline officials' low proactive disposition mediates policy implementation failure. Instead of proactive responsiveness (anticipating minor damage), officials often exhibit passive responsiveness (acting only after major incidents or reports), leading to a critical breakdown in which administrative procedures are completed but the public outcome remains poor. The novelty of this research lies in proposing a Proactive and Participatory Governance Model. This model necessitates the institutionalisation of Public Involvement (Participation) to enhance transparency and shift asset performance evaluation from output-oriented to outcome-oriented. The study concludes that the optimal model for the Ponorogo Transportation Department is the synergy between agile asset management and NPS principles (proactive and participatory) to enhance public service effectiveness.